2021
DOI: 10.1007/s11258-021-01203-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in floristic and trait composition along environmental gradients in the herb layer of temperate forests in the transition zone between Central and SE Europe

Abstract: Species- and trait-environment linkages in forest plant communities continue to be a frequent topic in ecological research. We studied the dependence of floristic and functional trait composition on environmental factors, namely local soil properties, overstory characteristics, climatic parameters and other abiotic and biotic variables. The study area comprised 50 monitoring plots across Slovenia, belonging to the EU ICP Forests monitoring network. Vegetation was surveyed in accordance with harmonized protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…arundinacea (Schrank) K. Richt, ferns Pteridium aquilinum (L.) Kuhn, Blechnum spicant (L.) Roth and berries Vaccinium myrtillus and V. vitis-idaea are common. In some of the study plots, the forest floor was almost completely covered by these species (Kermavnar and Kutnar 2020;Kermavnar et al 2021aKermavnar et al , 2021b. This is consistent with an experimental study of traits in which the bryophyte specific shoot length increased with increasing vegetation height and litter cover, indicating stronger competition from vascular plants (Van Zuijlen et al 2021).…”
Section: Functional Trait Composition and Diversitysupporting
confidence: 88%
“…arundinacea (Schrank) K. Richt, ferns Pteridium aquilinum (L.) Kuhn, Blechnum spicant (L.) Roth and berries Vaccinium myrtillus and V. vitis-idaea are common. In some of the study plots, the forest floor was almost completely covered by these species (Kermavnar and Kutnar 2020;Kermavnar et al 2021aKermavnar et al , 2021b. This is consistent with an experimental study of traits in which the bryophyte specific shoot length increased with increasing vegetation height and litter cover, indicating stronger competition from vascular plants (Van Zuijlen et al 2021).…”
Section: Functional Trait Composition and Diversitysupporting
confidence: 88%
“…We opted for: tree layer shade-casting ability (EIV-L), mean annual temperature (EIV-T), soil moisture (EIV-F), soil pH (EIV-R) and total nitrogen content in the soil (EIV-N). All these variables were available from our previous study (Kermavnar et al 2022). In the Results section, the variable with higher explanatory power is presented.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that we considered only woody plants in the tree communities, whereas Bruelheide et al (2018) included understorey plants, such as herbaceous plants and shrubs, in forests. The trait composition of the understorey layer is influenced by not only the environment (Cubino et al, 2021), but also canopy shading (Kermavnar et al, 2021). Recently, studies have also found variable trait–environment relationships between trees and herbs (Simova et al, 2018; Cheng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%